KONSEP MAKNA NAMA-NAMA AL-QUR'AN DALAM MUSHAF ‘UTSMANI (STUDI TAFSIR MAUDHU’I) - Firmansyah, Reza; Muttaqin, Ja'far; Sabarudin, Ikbal (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2022)
The study of "names" has become a topic of endless discussion, as is the other name of the Al-Qur'an which shows its majesty and holiness compared to other holy books that were revealed to the previous prophets. This study aims to discuss the meaning of the names of the Qur'an in the Mushaf 'Uthmani with the Maudhu'i interpretation method. The theory used is the Maudhu'i interpretation. This research method is a qualitative type through literature study using content analysis. This research concludes that the concept of the meaning of the names of the Qur'an in the 'Uthmani Mushaf' which has been examined by the author in this study is found from every other name with a very wide variety of meanings, this proves that the Qur'an is a great miracle. which Allah bestowed upon the Islamic ummah. As for the signs of His power through another name from the Al-Qur'an, there are values for the meaning of its own function, nature, and role for the Al-Quran. Methodologically, the author in this article quotes Maudhu'i M. Quraish Shihab's step of the interpretation by collaborating the steps commonly used by Al-Farmawi.